The Metaphorical Conceptualization of Depression in Arabic Blogs Written by Patients with Depressive Disorder - Abu Rumman, Ronza; Dagamseh, Mohammed; Haider, Ahmad S; Saed, Hadeel; Sahari, Yousef (Forum for Linguistic Studies, 2025)
This study aims to identify the conceptual metaphors of depression in a corpus of 100 blogs written in Arabic by people suffering from major depressive disorder by adopting the Conceptual Metaphor Theory. Metaphor Identification Procedure was used to identify metaphorical expressions, and then the five-step procedure proposed by Steen was employed to extract the conceptual metaphors. The results revealed three main categories of metaphors: metaphors of depression, metaphors of interpersonal communication and social context, and metaphors of medicine and professional treatment. The study concluded that blogging as a genre provides individuals with the opportunity to give more truthful descriptions of their illness, which enables them to present a more thorough picture of their lives with depressive disorder.